Analisa Pengaruh Putaran Pada Mesin Pencacah Rumput Gajah Pakan Ternak - Manurung, Marito Yanti; Sianturi, Tambos; Naibaho, Winfrontstein (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2023)
(Elephant grass is the most common food ingredient consumed by livestock, such as goats or lemurs. In this final project, we will analyze variations in the rotation of the elephant grass chopper by calculating the machine elements. The steps taken for this purpose are: observing the existing enumerator, assembling the tool and then testing the tool. So you can find out the capacity of the machine. The results of calculations and discussions concluded that F0 determines how much torque and power. The belt selected is a v-belt type A, pulley diameter I (70 mm), II (97 mm). With the results of chopping that can be obtained the standard for animal feed is 5.8 cm. then the capacity obtained from the elephant grass chopper is 21 kg/hour. Keywords: Belt, diameter, grass, torque